Investigation the complement level in abortive women with antiphospholipid syndrome - Salih, Manal B. (University of Thi-Qar Journal of Science, 2014)
The present study included 100 women with recurrent miscarriage and more than once due to antiphospholipid antibodies, and who are in the age range between (20-40) years and their comparison with 100 women with normal pregnancy and negative for the disease, by using enzyme-linked Immunosorbent assay (ELISA), for the detection of positive cases of autoimmune disease. The results showed for antiphospholipid antibodies and antibody within the Group (IgM) to the highest rate recorded in the first group (70%) and age group (31-35) years , and for the Group (IgG), the highest rate recorded in the first group (50%) and in the age (26-30) years. As can be seen from these results that the percentage of complement in this study was low compared with control